2012
DOI: 10.1371/journal.pone.0040935
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Smallest Active Fragment of HsQSOX1b and Finding a Highly Efficient Oxidative Engine

Abstract: Human quiescin-sulfhydryl oxidase 1 isoform b (HsQSOX1b) is a highly efficient, multiple-domain enzyme that directly inserts disulfide bonds into client protein. However, previous studies have focused mainly on the catalytic activity of the whole protein rather than its domain structure. In this research, we dissected the structure and function of HsQSOX1b and explored its mechanism as a highly efficient sulfhydryl oxidase by analyzing the truncated variants. The results showed that the first HsQSOX1b thioredo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…The retaining of the main functional domains of the protein and all of the redox-active disulfides in the isoforms QSOX1 c,d,e may preserve the main function of the enzyme - the oxidation of sulfhydryl groups to disulfides by reducing oxygen to hydrogen peroxide. This assumption is in agreement with the recently published functional studies of QSOX1 fragments which indicated the importance of interaction of the Trx and ERV/ALR domains for the thiol-oxidation activity of the QSOX1 protein [37], [38]. The products of the remaining splice variants ( QSOX1 f-i) lack all but the N-terminal fragment of the Trx1 domain and are most likely dysfunctional proteins.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The retaining of the main functional domains of the protein and all of the redox-active disulfides in the isoforms QSOX1 c,d,e may preserve the main function of the enzyme - the oxidation of sulfhydryl groups to disulfides by reducing oxygen to hydrogen peroxide. This assumption is in agreement with the recently published functional studies of QSOX1 fragments which indicated the importance of interaction of the Trx and ERV/ALR domains for the thiol-oxidation activity of the QSOX1 protein [37], [38]. The products of the remaining splice variants ( QSOX1 f-i) lack all but the N-terminal fragment of the Trx1 domain and are most likely dysfunctional proteins.…”
Section: Discussionsupporting
confidence: 91%
“…Although initially identified as being strongly up-regulated in fibroblasts reaching confluence, it has also been since associated with growth factor activity, and it is highly expressed in cells with a large secretory load [12]. In different studies on QSOX1 a variety of functions have been ascribed to this enzyme including protection from apoptosis [11], [12], [39][42] and facilitation of tumour cells invasion [38]. Thus, the forced overexpression of quiescin 6 in human MCF-7 breast cancer cells rendered them more resistant to apoptosis arising from oxidative stress compared to control transfected cells, thereby implicating QSOX1 in cell survival [11] whilst the suppressed expression of quiescin in pancreatic cancer cell lines BxPC-3 and Panc-1 inhibited cancer cell invasion by activation of MMP-2 and MMP-9 Matrix Metalloproteinases [43].…”
Section: Discussionmentioning
confidence: 99%
“…How ebselen inhibits QSOX1 through interaction with these residues is unclear because they are not thought to participate in the accepted disulfide relay mechanism. There is no evidence supporting cysteines other than the redox-active C-X-X-C motifs in the Trx1 and Erv domains as contributing to QSOX1 activity [ 11 , 18 , 32 34 ]. C237 is likely protonated and relatively inert to redox reactions since there are no nearby basic residues to stabilize a thiolate anion [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sulfhydral oxidase activity of rPbQSOX was determined at 25°C in 50 mM potassium phosphate buffer and 1 mM EDTA at pH 7.5 as described elsewhere (Raje et al, 2002 ; Zheng et al, 2012 ). The molar concentration of the enzyme was determined according to the molecular weight determined using the molar extinction coefficient from the ExPASy proteomics server ( http://www.expasy.org/ ).…”
Section: Methodsmentioning
confidence: 99%